2014
DOI: 10.1016/j.febslet.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglycerol biosynthesis is required for the development of embryos and normal membrane structures of chloroplasts and mitochondria in Arabidopsis

Abstract: Edited by Ulf-Ingo FlüggeKeywords: Chloroplast Development Embryo Mitochondrion Phosphatidylglycerol Phospholipid a b s t r a c t Phosphatidylglycerophosphate (PGP) synthase, encoded by PGP1 and PGP2 in Arabidopsis, catalyzes a committed step in the biosynthesis of phosphatidylglycerol (PG). In this study, we isolated a pgp1pgp2 double mutant of Arabidopsis to study the function of PG. In this mutant, embryo development was delayed and the majority of seeds did not germinate. Thylakoid membranes did not develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…In Arabidopsis, two enzymes are thus responsible for PG synthesis: Phosphatidylglycerophosphate synthase1 (PGP1), localized in both chloroplast and mitochondria (Babiychuk et al, 2003), and PGP2, localized in the ER (Müller and Frentzen, 2001). By studying pgp mutants, it was established that the PGP1-dependent pathway was responsible for 70% of PG synthesis in leaves and was required for the development of green leaves and chloroplasts with well-developed thylakoid membranes Xu et al, 2002), whereas the pgp2 mutant showed a small decrease in PG content compensated by a slight increase in PI content (Tanoue et al, 2014). Based on the facts that PG and PI biosynthesis pathways share their precursors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, two enzymes are thus responsible for PG synthesis: Phosphatidylglycerophosphate synthase1 (PGP1), localized in both chloroplast and mitochondria (Babiychuk et al, 2003), and PGP2, localized in the ER (Müller and Frentzen, 2001). By studying pgp mutants, it was established that the PGP1-dependent pathway was responsible for 70% of PG synthesis in leaves and was required for the development of green leaves and chloroplasts with well-developed thylakoid membranes Xu et al, 2002), whereas the pgp2 mutant showed a small decrease in PG content compensated by a slight increase in PI content (Tanoue et al, 2014). Based on the facts that PG and PI biosynthesis pathways share their precursors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Here, C. reinhardtii has two annotated PGPSs, PGP1 and PGP2 (Riekhof et al, 2005). A. thaliana also has two PGPSs, PGP1 and PGP2, with PGP1 as the major contributor to the chloroplast PG biosynthesis Xu et al, 2002;Tanoue et al, 2014). Finally, PGP is dephosphorylated by PGPP to produce PG, and CrPGPP1 is revealed as a functional PGPP in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…PCC 6803, affects cell growth and photosynthetic activity unless PG is supplemented exogenously Sato et al, 2000;Gombos et al, 2002). Arabidopsis possesses two PGPSs, PGP1 and PGP2; knocking out PGP1 severely affects photosynthesis but not the mitochondrial function Xu et al, 2002;Babiychuk et al, 2003;Kobayashi et al, 2014), and double knockout of PGP1 and PGP2 further reduces PG levels to trace amounts, thereby affecting overall plant growth (Tanoue et al, 2014). The importance of PG in mitochondria is suggested by the study of CL synthase (CLS), in that Arabidopsis CLS1 is localized at mitochondria and required for mitochondria function (Katayama et al, 2004;Pineau et al, 2013;Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PG is required for embryo development [83], photosynthesis [84] and thylakoid membrane development [85]. These roles are reflected in the subcellular and tissue distribution of PG.…”
Section: Plantsmentioning
confidence: 99%